Penilaian Pengetahuan Masyarakat tentang Swamedikasi Gastritis: Studi Cross-Sectional Nasional di Indonesia: Assessing Community Knowledge on Gastritis Self-Medication: A Nationwide Cross-Sectional Study in Indonesia - Hikmah, Nurul; Utami, Pinasti; Octavia, Mega; Rahajeng, Bangunawati; Ramadhani, Firda Ratnasari; Prameswara, Annisaa Bella; Charismawati, Erlinda Mimbar; Diastri, Hanna (Program Studi Farmasi-Fakultas Matematika dan Ilmu Pengetahuan Alam-Universitas Tulang Bawang, 2025)
Gastritis is a common gastrointestinal disorder that affects global population, including Indonesia. Many individuals choose self-medication as a primary approach to manage gastritis symptoms. Inappropriate self-medication practices can lead to worsening symptoms and complications. Understanding the knowledge level is essential to improve self-medication safety. This study aims to assess the level of community knowledge regarding gastritis self-medication in Indonesia. An observational study with cross-sectional design conducted among Indonesia community. Data were collected through an e-questionnaire, which was distributed across 34 provinces. The instrument in this study has been tested for validity and reliability using Content Validity, Face Validity, and Cronbach's Alpha tests. Descriptive statistical analysis was performed using SPSS to summarize the characteristics of the respondents and to categorize knowledge levels into low, moderate, and high. The results of this study indicated that 921 respondents (78.1%) had a high knowledge level, 247 respondents (21%) had a moderate knowledge level, and 11 respondents (0.9%) had a low knowledge level of gastritis self-medication. In conclusion, knowledge level of Indonesian community regarding gastritis self-medication is categorized as high. Limited number of respondents still have low to moderate knowledge level, indicating the necessity for further roles and strategies from healthcare professionals in gastritis self-medication education. Keywords: Gastritis, Knowledge, Self-medication, Indonesia